The Concept and Practice of Macroprudential Policy in Indonesia: Islamic and Conventional - Sakti, Muhammad Rizky Prima; Thas Thaker, Hassanudin bin Mohd; Qoyum, Abdul; Qizam, Ibnu (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2018)
This study aims to examine reserve ratio (GWM), and capital buffer toward credit growth; the impact of macroeconomic variables and micro-banking specific factors toward credit growth in Islamic and Conventional Bank. This research using Vector Error Correction Model (VECM). This research finds that macroprudential policy based on GWM instrument positively influence the credit growth of conventional and Islamic banks. From macroeconomic, the credit growth is positively affected by GDP and negatively affected by BI Rate and inflation. Also, credit also affected by deposit funds and default rate ratio. Interestingly, there is a different impact of capital buffer instrument toward credit growth. Capital buffer instrument has negatively affected the financing growth of Islamic banks in Indonesia.DOI: 10.15408/aiq.v10i1.5446